2012
DOI: 10.1080/13683500.2011.628013
|View full text |Cite
|
Sign up to set email alerts
|

Young tourists, gender and fear on holiday

Abstract: This paper addresses, through in-depth interviews and long-term observations, how young men and women perceive fear of crime and violence on holiday. Although many studies have highlighted a difference between males and females with regard to the expression of fear, gendered differences and similarities in the perception and expression of fear have remained largely unexplored within the context of tourism. The results show that gender, despite having been traditionally constructed as a binary concept, did not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 68 publications
0
5
0
Order By: Relevance
“…These accounts reflect an increasing awareness of the non-heterosexual orientations in Asian societies and further support the understanding that sexual risk is far less an arousal-induced risk but a manifestation of the power and dominance of the hegemonic masculinities over the others, which include the feminine and the "less" masculine (Brownmiller, 1975;Sivakumaran, 2005). This finding adds ramifications to existing understanding of risk and gender in tourism where the gender differences in risk are often discussed as a dichotomous concept, neglecting the effect of risk on multiple femininities and masculinities along the gender and sexual orientation spectrums (Mura & Khoo-Lattimore, 2011). Accordingly, future research is encouraged to explore the risk perception of solo travellers with different gender identities and sexual orientations.…”
Section: A Multidimensional Gendered Riskmentioning
confidence: 99%
“…These accounts reflect an increasing awareness of the non-heterosexual orientations in Asian societies and further support the understanding that sexual risk is far less an arousal-induced risk but a manifestation of the power and dominance of the hegemonic masculinities over the others, which include the feminine and the "less" masculine (Brownmiller, 1975;Sivakumaran, 2005). This finding adds ramifications to existing understanding of risk and gender in tourism where the gender differences in risk are often discussed as a dichotomous concept, neglecting the effect of risk on multiple femininities and masculinities along the gender and sexual orientation spectrums (Mura & Khoo-Lattimore, 2011). Accordingly, future research is encouraged to explore the risk perception of solo travellers with different gender identities and sexual orientations.…”
Section: A Multidimensional Gendered Riskmentioning
confidence: 99%
“…It has also been noted in fear-related studies that the concept of fear can be split into five main categories of risk, namely, political, environmental, health, planning and property. Overall, analyses of the concept have highlighted that, in the context of travel and tourism, fear is associated with several different factors, including fear of crime, of travelling and flying and of diseases (Dolnicar, 2005b;Fennell, 2017;Korstanje, 2011;Leung et al, 2018;Mawby, 2000;Mizrachi and Fuchs, 2016;Mura and Khoo-Lattimore, 2012).…”
Section: Phobiamentioning
confidence: 99%
“…How tourists perceive risk will affect their travel decisions such as destination selection and itinerary planning, be they positive or otherwise. The existing literature has generally agreed that tourists tend to avoid destinations with greater perceived risks (Batra, 2008; Law, 2006; Sönmez et al., 1999), although a number of studies have found that some tourists would intentionally seek to participate in risky activities and visit risky destinations (Dickson and Dolnicar, 2004; Fuchs et al., 2013; Mura and Khoo-Lattimore, 2011). The disagreement on risk perception and travel decision merits further investigation.…”
Section: Literature Reviewmentioning
confidence: 99%